Sensory Profile of Nepalese Children with or without Autism - Shrestha, Merina; Shrestha, Rena (Journal of Nepal Paediatric Society, 2022)
Introduction: Sensory Integration Dysfunction (SID) is common in children with Autism Spectrum Disorder. If SID is detected early and intervened, there is a decrease in autistic mannerisms and an improvement in the areas of sensory processing and regulation, social-emotional function, and fine motor skills. Thus, this study was conducted to compare the sensory profile of children with or without autism spectrum disorder (ASD) in Nepal. Methods: Thirty five parents of children with ASD and 43 parents of children without ASD (non ASD) completed Short Sensory Profile (SSP) questionnaire. Results: Definitive sensory issue was identified in 66% in ASD and 23% in non ASD group. Common sensory issues in ASD group were auditory filtering sensitivity (74.3%), movement sensitivity (37%), under responsiveness / seeks sensation (45.7%). In non ASD group, common sensory issue was under responsive/seek sensation. The internal consistencies between the sub-scales ranged from 0.70 to 0.83. Conclusions: Two third of the children with ASD have sensory issues. Identifying different sensory problems with SSP would be helpful for further management of children with ASD.